Advances in the synthesis and relationship with fermentation of Monacolin K genes in Hongqu - CHEN Ruonan, FENG Rui, ZHOU Heng, HU Qing, JI Shen, WANG Shaomin (Zhongguo niangzao)
Hongqu, as a fermented product with lipid-lowering effect, is produced by fermentation with Monascus and rice. Monacolin K, the most representative lipid-lowering component in Hongqu, is synthesized through the synergy of 9 genes (mokA to mokI), with the genes mokA and mokB being the key genes in this synthesis pathway. The fermentation process influences the expression of genes related to Monacolin K, thereby increasing its content in Hongqu to meet the growing market demand. In this paper, various factors affecting the synthesis of Monacolin K were comprehensively explored, including genes, synthetic pathways, and the effects of fermentation conditions on gene expression. Through an in-depth analysis of these elements, it was expected to provide references for the future study on the metabolic regulation of Monacrin K and its efficient use in industrial production, and laid a solid foundation for the further development and commercial application of Hongqu industry.